Quinta do Formigal. Análise, Reflexão,Transformação - Francisco da Gama Gonçalves Pereira (2016)
We present a proposal for the transformation of aleisure farm in Alentejo, Portugal ("quinta de recreio alentejana").Throughout this work, we have studied the farm itself, thecharacteristics of the architecture in the region, as well asrenewal and original architecture projects, both related to touristicenterprises. This investigation has influenced our proposal for arural tourism, as requested by our clients.